Comparison of antioxidant activity of compounds isolated from guava leaves and a stability study of the most active compound. - Nantitanon W. (2014)
In the present study, quercetin (QT), morin (MR), and quercetin-3-O-glucopyranoside (QG) isolated from guava leaves were comparatively tested for antioxidant activity using DPPH, ABTS, and FRAP methods. QT was the most active among them. The free radical scavenging activity of QT was approximately four times higher than MR and two times higher than QG. The reducing power of QT was eight times higher than MR and two times higher than QG. A mixture of QT with MR or QG showed interesting combination effect. The synergistic antioxidant activity was obtained when QT was mixed with MR whereas the antagonistic effect was found when mixed with QG. The stability study of QT in liquid preparations indicated that the decomposition reaction rate of QT could be explained by a kinetic model assuming a first-order chemical reaction. The aqueous solution of QT was rapidly decomposed with t1/2 of approximately five days whereas QT entrapped in chitosan nanoparticles was five times longer. It was concluded that QT was the most active antioxidant from guava leaves. Entrapment of QT in chitosan nanoparticles could significantly enhance its stability.